Floristic characteristics of sub-Pannonian grassland in Bistrinci (East Croatia) : Florističke značajke subpanonskog travnjaka u Bistrincima (Istočna Hrvatska) - Rašić, Sanda (Array, 2022)
Continental dry grasslands are important habitats that are among the endangered vegetation types not only in Croatia but also in the countries of Central and Western Europe. Areas under grassland are decreasing year to year due to the decreasing traditional way of using them (mowing and grazing). Reducing the loss of grassland is a strategic goal and flora inventory is one way to protect them from extinction. Overgrown surfaces lead to a progressive succession of vegetation. The aim of this research is to determine the floristic composition of sub-Pannonian grasslands and to isolate invasive species. The research was conducted during the vegetation in 2020 and 2021, and 122 taxa from 37 families were identified.